Analysis of The Implementation of The Regulation of The Minister of Agrarian and Spatial Planning Number 5 of 2020 in Electronic Registration of Mortgage Rights (Study of Mortgage Rights Registration by PPAT) - Ayunda Oktaviani (Faculty of Law, Universitas Negeri Semarang, 2025)
This study aims to analyze the implementation of the Regulation of the Minister of Agrarian Affairs and Spatial Planning Number 5 of 2020 concerning electronic mortgage services (HT-el) in Indonesia, with a focus on the role of PPAT and its impact on the mortgage registration process. The method used is qualitative with an empirical legal approach, through interviews, direct observation, literature studies, and analysis of related laws and regulations. The results of the study indicate that the HT-el system improves the efficiency, security, and transparency of land services, speeds up the process from months to around 7 days, and reduces costs and facilitates access. However, the implementation of this system faces obstacles such as system disruptions, data synchronization failures, and adaptation challenges from officials and debtors. Education, mentoring, and improving infrastructure and human resource capacity are needed to ensure the success of this digital transformation. This study emphasizes the importance of technological modernization in land administration in order to improve service quality and reduce the potential for document misuse.